Pengaruh Profitabilitas dan Struktur Aktiva Terhadap Struktur Modal Di Perusahaan Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Wahyuni, Rezza; Dewi, Mike Kusuma (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
The capital structure is an illustration of the company's financial proportions, namely between owned capital that comes from long-term debt and own capital which is a source of financing for a company. The purpose of this study is to determine the effect of profitability on capital structure and the effect of asset structure on capital structure in food and beverage companies listed on the Indonesia Stock Exchange in 2017-2021. The method used in this research is quantitative. The sample in this study used purposive sampling and obtained 11 companies. The analysis technique in this research is panel data regression. Based on the results of the study, it shows that profitability has no effect on capital structure and asset structure has a positive and significant effect on capital structure ratios.